A validated instrument measuring students' perceptions on plastinated and three‐dimensional printed anatomy tools. Issue 5 (17th January 2022) - Chandrasekaran, Ramya; Radzi, Shairah; Kai, Peh Zhen; Rajalingam, Preman; Rotgans, Jerome; Mogali, Sreenivasulu Reddy
Abstract: Due to the modernization of the medical curriculum and technological advancements, anatomy education has evolved beyond cadaveric dissection alone. Plastination techniques, three‐dimensional (3D) modeling, and 3D printing technologies have progressively gained importance. However, there are limited valid and reliable surveys to evaluate students' perceptions of these new anatomy tools. Hence, this study aimed to develop a validated instrument to measure students' learning satisfaction, self‐efficacy, humanistic values, and perceived limitations of plastinated and 3D printed models. A 41‐item survey (five‐point Likert scale, 1 = strongly disagree to 5 = strongly agree) was administered to Year 1 undergraduate medical students following a randomized controlled crossover study that evaluated plastinated and 3D printed cardiac and neck models. Ninety‐six responses were received, and a factor analysis was performed with the Kaiser–Meyer–Olkin sampling adequacy of 0.878. The confirmatory factor analysis yielded a 4‐factor, 19 items model that had a good fit with the latent constructs of x 2 (147) = 211.568, P < 0.001, root mean square error of approximation = 0.068, root mean square residual = 0.064, comparative fit index = 0.946, and Tucker Lewis index = 0.937. The Cronbach's alpha for the individual factors ranged from 0.74 to 0.95, indicating good internal consistency. This demonstrated a psychometrically valid and reliable instrument to measure students' perceptions toward plastinated and 3D printed models.